1998
DOI: 10.1111/j.1444-0938.1998.tb06747.x
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for non‐selective colour channel involvement in diabetic eyes especially after laser treatment

Abstract: Purpose:We consider the hypothesis that proliferative diabetes produces selective loss of colour channels. We also consider the possibility that laser treatment for this condition does not affect macula function. Methods: We tested for the possibility of a selective colour channel involvement in 35 eyes of 33 cases of proliferative diabetes by considering the outcomes of saturation and hue testing before and after pan-retinal photocoagulation (PRP). Saturation testing was achieved with the Sahlgren Saturation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2010
2010
2010
2010

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…The colour perception, in fact, improved in subjects operated of phacoemulsification and implantation of intra-ocular lens (IOL) with blue light filter. 50 In 1998, Mahon and colleagues 51 concluded that untreated eyes with proliferative retinopathy had deficits in the discrimination of hue more pronounced then light sensitivity. The laser treatment (pan-retinal photocoagulation [PRP]), according to the authors, seemed to produce a paradoxical normalisation of the perception of light (saturation) but a still impaired chromatic sensitivity.…”
Section: Colour Sensitivity Testsmentioning
confidence: 99%
“…The colour perception, in fact, improved in subjects operated of phacoemulsification and implantation of intra-ocular lens (IOL) with blue light filter. 50 In 1998, Mahon and colleagues 51 concluded that untreated eyes with proliferative retinopathy had deficits in the discrimination of hue more pronounced then light sensitivity. The laser treatment (pan-retinal photocoagulation [PRP]), according to the authors, seemed to produce a paradoxical normalisation of the perception of light (saturation) but a still impaired chromatic sensitivity.…”
Section: Colour Sensitivity Testsmentioning
confidence: 99%